Developments measurements of TEM sounding in China. (2nd July 2019) - Xue, Guoqiang; Zhang, Linbo; Zhou, Nannan; Chen, Weiying
Abstract : China is facing many challenges in the area of high‐precision exploration for deep mineral resources, and also in environmental and engineering fields. It has become an urgent task to realize geophysical explorations with high precision and high efficiency in complex environments. It has been found that the traditional transient electromagnetic method (TEM) had a series of problems related to theory, method, and instrument, as well as data interpretation. Based on the reviews of present TEM achievements, three new improved measurements are introduced. The central‐loop system was improved by a large fixed‐loop system; the long‐offset system was changed to the short‐offset one; the resistivity profile was transformed into a virtual wave‐field profile. Finally, this paper points out that the future research direction of the TEM method is in terms of equipment, data processing, and big data information.